1982
DOI: 10.1007/bf01655364
|View full text |Cite
|
Sign up to set email alerts
|

The management of the hypoglycemic patient

Abstract: Organic hypoglycemia may be caused by an insulinoma. This is a rare tumor, multiple in about 10% and malignant in about 10% of cases. Multiplicity is particularly likely when insulinoma occurs as part of the MEN 1 syndrome. When a patient exhibits Whipple's triad, synchronous blood sugar and insulin estimations must be made, and repeated during fasting. Diagnosis depends on the finding of inappropriately high insulin levels in the presence of low blood sugars. Many stimulatory tests are available but none are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…It is not significantly more expensive to study the pancreas after the liver, even though only 1 tumor in 5 will be found, and these tumors found have a diameter in excess of 10 mm [5]. Computed tomographic scanning hardly appears to be more useful than ultrasound and is much more expensive [6][7][8][9]. In our view, CT scanning for insulinoma should be abandoned in routine practice and used only in those research centers with the most modern equipment [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is not significantly more expensive to study the pancreas after the liver, even though only 1 tumor in 5 will be found, and these tumors found have a diameter in excess of 10 mm [5]. Computed tomographic scanning hardly appears to be more useful than ultrasound and is much more expensive [6][7][8][9]. In our view, CT scanning for insulinoma should be abandoned in routine practice and used only in those research centers with the most modern equipment [10].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical management is strongly influenced by the morphological features of the tumor on the one hand and the possibilities of localization on the other [36]. Fourteen percent of these tumors have sizes less than 1 cm and cannot be visualized preoperatively, despite good diagnostic procedures [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Among 72 patients, published from the Mayo Clinic, only 2 had Whipple procedures [2]. Most authors agree that the Whipple procedure is too radical a therapy for a benign insulinoma of the head of the pancreas [3,18]. In this multiinstitutional review, enucleation was the procedure of choice for insulinomas in the head of the pancreas.…”
Section: Outcomementioning
confidence: 97%